Boulevard to broken dreams, Part 2: implementation of the Polonoroeste road project in the Brazilian Amazon, and the World Bank’s response to the gathering storm - H. Wade, Robert (Brazilian Journal of Political Economy, 2016)
This is the second part of the essay on the circumstances that led the World Bank to embrace norms and operational policies for environmental and indigenous people’s protection in the late 1980s, as traced through the turbulent history of the Polonoroeste road project in the Brazilian Amazon. Polonoroeste became the spearhead with which environmental NGOs made their first attack on the Bank for participating in large-scale environmental and indigenous peoples’ destruction. JEL Classification: Q5; O13; I3.